HNSCC cell lines positive for HPV and p16 possess higher cellular radiosensitivity due to an impaired DSB repair capacity - Rieckmann, Thorsten; Tribius, Silke; Grob, Tobias J.; Meyer, Felix; Busch, Chia-Jung; Petersen, Cordula; Dikomey, Ekkehard; Kriegs, Malte (Radiotherapy and oncology, 2013)
When treated by radiotherapy, patients with squamous cell carcinomas of the head and neck (HNSCC) positive for HPV and p16INK4a possess a clearly favorable prognosis as compared to those with HPV-negative HNSCC. The aim of this work was to study whether the better outcomes might be caused by an enhanced cellular radiosensitivity. The radiation response of five HPV/p16INK4a-positive and five HPV-negative cell lines was characterized with regard to cellular radiosensitivity by colony formation assay. Furthermore G1- and G2-arrest, apoptosis and residual DNA double-strand breaks (DSB) were analyzed by the colcemid-based G1-efflux assay, propidium iodide staining, the detection of PARP cleavage, the fluorescence-based detection of caspase activity and the immunofluorescence staining of γH2AX and 53BP1 foci. On average, the cellular radiosensitivity of the HNSCC cell lines positive for HPV and p16INK4a was higher as compared to the sensitivity of a panel of five HPV-negative HNSCC cell lines (SF3=0.2827 vs. 0.4455). The higher sensitivity does not result from increased apoptosis or the execution of a permanent G1-arrest, but is rather associated with both, elevated levels of residual DSBs and extensive G2-arrest. Increased cellular radiosensitivity due to compromised DNA repair capacity is likely to contribute to the improved outcome of patients with HPV/p16INK4a-positive tumors when treated by radiotherapy.